ความคล่องตัวโซ่อุปทานและความหยุ่นตัวโซ่อุปทาน: การนำไปใช้สำหรับโซ่อุปทานอุตสาหกรรมคอมพิวเตอร์ในประเทศไทย - เศรษฐโชติสมบัติ, ณัฎภัทรศญา (Academic Journal Phranakhon Rajabhat University, 2017)
The purposes of this research were to study 1) To identify and classify between Supply Chain Agility(SCA) and Supply Chain Resilience (SCR), which are commonlystrategy applied in the supply chain of computer industry in Thailand.2) To study the relationships among Agility, Resilience, and Firm's performanc (FP) in the supply chain of computer industry in Thailand.3) To identify and examine the differences across organizational characteristics on Agility, Resilience, and Firm's performanc an implementation in the organiztion.By using to mixed of research methodology, among qualitative and quantitative methods. For qualitative method using deep interview for collecting insights from manufacturers and distributors in the computer industry in Thailand in order to obtain quality information, from 6 companys and 12 population. And quantitative method using the questionnaires totals 560 companys and 1,120 populations, with stratified random sampling, data analyze by various statistical techniques to ensure reliability and validity in structural equation modeling (SEM) The findings found that, 1)SCR has commonly strategy applied in the supply chain of computer industry in Thailand. But it consider from indirect effect found that, SCR has appropriate. However, SCR has positive effect directly and indirectly to FP, which better than.2) Found that relationships on positive effect directly among SCA and SCR, SCR and FP. Furthermore, found that indirect effect among SCR and SCA, SCA and FP, SCR and FP.3) Found backward relationship among SCA and SCR, including, if apply SCA and SCR in parallel, will be strong positive effect to FP.